Gender Equality and Its Spill over Effects on Education, Employment, and Institutions within Sustainable Development: An Indian Perspective - L, Jeena; Pynadath, Minnu F. (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
As the world approaches the 2030 deadline for the Sustainable Development Goals (SDGs), gender equality remains essential for inclusive and sustainable growth. No country can progress socially or economically without ensuring equal opportunities for women and men. India, with its vast and diverse population, plays a key role in achieving SDG 5 globally. Despite multiple policy initiatives, significant gender disparities persist across states, affecting education, employment, and institutional effectiveness. This study evaluates India’s progress toward gender equality by analysing SDG 5 and its linkages with SDGs 4 (Quality Education), 8 (Decent Work), and 16 (Peace and Justice). Using SDG indicators and text analytics of government schemes and reports, the research applies clustering, network analysis, topic modelling, sentiment analysis, and N-gram mapping across 28 states and 8 Union Territories from 2018 to 2024. Findings highlight key indicators such as sex ratio at birth, female labour force participation, and pupil-teacher ratios as critical drivers of development. While some states show steady progress, others face persistent structural challenges. The study further integrates ESG dimensions and provides actionable policy recommendations to enhance gender-responsive development.